2018
DOI: 10.1021/acs.biochem.7b00887
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Intermediates of Nitric Oxide Synthase from Deinococcus radiodurans as Revealed by Pulse Radiolysis: Evidence for Intramolecular Electron Transfer from Biopterin to FeII–O2 Complex

Abstract: Nitric oxide synthase (NOS) is a cytochrome P450-type mono-oxygenase that catalyzes the oxidation of l-arginine (Arg) to nitric oxide (NO) through a reaction intermediate N-hydroxy-l-arginine (NHA). The mechanism underlying the reaction catalyzed by NOS from Deinococcus radiodurans was investigated using pulse radiolysis. Radiolytically generated hydrated electrons reduced the heme iron of NOS within 2 μs. Subsequently, ferrous heme reacted with O to form a ferrous-dioxygen intermediate with a second-order rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 89 publications
(183 reference statements)
0
5
0
Order By: Relevance
“…This process was similar to that observed during single-turnover reactions in stopped-flow measurements. 208 These results indicated that the intermediate observed after pulse radiolysis is the same intermediate during hydroxylation of Arg.…”
Section: Chemical Reviewsmentioning
confidence: 81%
See 4 more Smart Citations
“…This process was similar to that observed during single-turnover reactions in stopped-flow measurements. 208 These results indicated that the intermediate observed after pulse radiolysis is the same intermediate during hydroxylation of Arg.…”
Section: Chemical Reviewsmentioning
confidence: 81%
“…Schematic diagram showing intramolecular electron transfer from biopterin to Fe 2+ –O 2 (PDB code 1M7B). Reproduced from ref . Copyright 2018 American Chemical Society.…”
Section: Application Of Pulse Radiolysis To Biological Systemsmentioning
confidence: 91%
See 3 more Smart Citations